Characterization of the PSD of Activated Carbons by a Heterogeneous Surface Mixed Model - Alexandre de Oliveira, José Carlos (2013)
In this study, a model is proposed to calculate the Pore Size Distribution (PSD) of microporous activated carbons taking into account the defects as heterogeneity particles in the inner surface of each graphitic slit pore. We particularly examined the effects of surface heterogeneity in the determination of the PSD for a controlled series of microporous carbons prepared from peach stones as the precursor material. In order to obtain the PSDs of the samples, the Heterogeneous Surface Mixed Model (HSMM) on the basis of Grand Canonical Monte Carlo (GCMC) was used to generate simulated isotherms for the adsorption of N2 at 77 K and CO2 at 273 K. These results are compared with different models, like the Quenched Solid Density Functional Theory (QSDFT) and the Non Local Density Functional Theory (NLDFT) in order to check the self-consistency and robustness of the proposed model. It was found that our model is very flexible, allowing for the possibility of changing both the kind of heterogeneity particle and its coverage on the surface.